The efficacy of adding group behavioral activation to usual care in patients with fibromyalgia and major depression: design and protocol for a randomized clinical trial. - Gómez-Pérez, Lidia; Vergés, Alvaro; Vázquez-Taboada, Ana Rocío; Durán, Josefina; González Tugas, Matías (BMC, 2018)
Fibromyalgia (FM) and major depression frequently co-occur. Patients with both conditions have a worse prognosis and higher disability, and their treatment options are scarce. Behavioral activation (BA) may be a beneficial intervention for these patients, as it targets mechanisms of action that seem common to both disorders. Nevertheless, its efficacy has not been examined in people with both conditions. We describe the design and rationale of a randomized clinical trial aimed at evaluating the efficacy of adding BA (applied in groups) to usual care to reduce the severity of depressive symptoms (primary outcome) among Chilean women with FM and major depression (N = 90). Pain intensity, FM impact, pain catastrophizing and hypervigilance, physical health symptoms, environmental reward, and BA will be evaluated as secondary outcomes. Women will be randomized to an experimental arm (n =45) which will receive usual care (UC) for FM with comorbid depression plus BA; and a comparison arm, which will receive only UC for FM with comorbid depression (n = 45). Outcome assessment will take place at four-time points: (1) at baseline, (2) when the experimental arm is under treatment (between sessions 6 and 7), (3) immediately after the experimental arm completes the treatment, and (4) at a 3-month follow-up. We expect that, after treatment, the group receiving BA should experience greater reductions in the primary and secondary outcomes than the group receiving only UC. These reductions should be both statistically and clinically significant and will be maintained at follow-up. This study will contribute to facilitating the integrated treatment of fibromyalgia and depression.
Keywords: Fibromialgia - Aspectos psicológicos; Depresión mental; Terapia de conducta; Fibromyalgia; Depression; Behavioral activation; Group intervention; Efficacy; Chile